Finance, Talent Allocation, and Growth - Francesco D'Acunto; Laurent Frésard (Center for Economic Studies and ifo Institute (CESifo), 2018)
The growing finance wage premium is related to a modest net reallocation of skilled workers from non-finance sectors into finance in a broad sample of 24 countries over 35 years. The reallocation is higher when the finance wage premium grows faster than the contribution of the financial sector to the economy, which we proxy with the relative value added of finance. More innovative sectors and sectors exhibiting lower labor-transition costs face a higher reallocation of skilled workers. Yet, the growing finance wage premium is unrelated to sectoral or aggregate growth, to countries' innovative capacity, to student enrollment in STEM degrees, and to the riskiness, efficiency, and competitiveness of banking sectors. Overall, the reallocation of skilled labor implied by a growing finance wage premium appears too modest to materially affect economic growth.
Keywords: D72; G20; J23; J31; N20; 330; finance wage premium; skilled labor; misallocation; growth; innovation; banking sector.